The role of the church in ensuring peace and harmony in the society: A case study of Anglican church in Ogbunike, Anambra state, Nigeria - Ifeanyichukwu Micah Ezeokwuorah (Humanities Horizon, 2026)
Peace is widely regarded as a desirable goal for all societies, even in contexts where conflict appears inevitable. This study examines the role of the Church in promoting peace and harmony in society, using the Anglican Church in Ogbunike as a case study. Peace fosters constructive attitudes and purposeful actions that enable individuals to uphold justice, human rights, and harmonious coexistence. The study adopts descriptive, historical, and missiological research methods to analyze how the Church contributes to peacebuilding in Ogbunike. Both primary and secondary sources of data were utilized. Primary data were obtained through oral interviews with key informants and resource persons, eyewitness accounts, oral histories, and direct observations. Secondary data were sourced from books, journals, articles, magazines, documentaries, and relevant internet materials. Findings reveal that the Church employs several strategies to ensure peace and harmony in Ogbunike, including its supportive, preservative, protective, and prophetic functions. These strategies emphasize moral instruction, conflict resolution, advocacy for justice, and community engagement. The study further establishes that the Church plays a significant role in fostering good neighbourliness and preventing the escalation of conflicts within the community. The findings of this study are valuable to church leaders and authorities, as they provide a framework for restructuring and initiating effective peacebuilding programmes through seminars, conferences, and workshops for church workers and leaders. The study recommends that church leaders should take the lead in preaching and teaching the importance of peaceful coexistence, dialogue, and reconciliation. It also emphasizes the need to uphold core Christian values such as love, patience, kindness, moderation, and hospitality as essential tools for sustaining peace and harmony in Ogbunike.